Watchful witnesses : a study of the Crypt Memory and Witness Centre at St George's Cathedral and its Bearing Witness exhibition process - Greenwood, Megan (Social Anthropology, 2014)
This thesis examines four themes that surface through the Crypt Centre's activities towards its upcoming exhibition entitled Bearing Witness. The themes include the role of remembrance, bearing witness, the parameters of inclusions and exclusions, and the Crypt Centre's physical and symbolic significance.